1999
DOI: 10.1007/s004970050188
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous endosperm induction by in vitro culture of unfertilized ovules of Viola odorata L.

Abstract: Autonomous endosperm was found in unfertilized ovules of V. odorata L. cultured on MS medium supplemented with 2,4-D as a sole growth regulator or on media with 2,4-D and BAP or kinetin. Frequency of endosperm induction was approximately 9% in ovules analyzed. The induction rate depended mainly on genotype of the donor plant, and to lesser degrees, on floral stage, flower series and medium type. Multinuclear endosperms consisting of 10-37 nuclei were found in ovules after as few as 4 days of culture. In some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Additionally, evidence of a radial microtubule network was visible between AE nuclei, resembling a similar system described for an early nuclear stage of wild type endosperm. The patterns of AE development we observed in Arabidopsis repeated those reported in cultures of unpollinated ovules of Viola (Wijowska et al 1999b;Wijowska and Kuta, unpublished).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Additionally, evidence of a radial microtubule network was visible between AE nuclei, resembling a similar system described for an early nuclear stage of wild type endosperm. The patterns of AE development we observed in Arabidopsis repeated those reported in cultures of unpollinated ovules of Viola (Wijowska et al 1999b;Wijowska and Kuta, unpublished).…”
Section: Discussionsupporting
confidence: 83%
“…Bars in A-F=10 lm ovaries or isolated ovules of several wild, ornamental and cultivated plant species (Jensen et al 1977;Zhou and Yang 1981;Huang et al 1982;Mo´l 1993;Mo´l et al 1995;Wijowska et al 1999a, b;Wijowska and Kuta 2000;Rojek et al 2002). AE formed in vitro follows the formation of the secondary nucleus (Jensen et al 1977;Mo´l et al 1995) or results from divisions of unfused polar nuclei (Zhou and Yang 1981;Huang et al 1982;Mo´l et al 1995;Wijowska et al 1999b;Rojek et al 2002). Another possible pathway is the formation of atypical coenocytic female gametophytes with supernumerary nuclei, which may yield multinucleate endosperm-like structures directly (Mo´l 1993;Mó l et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agree to available reports for Suffruitcosum indiuom (Arunkumar et al, 2011). Also the favorable effect of using leaf explants for callus induction has already been reported by Stephan and Jayabalan (2000).Similarly, callus induction potential was found higher in leaves compared to stem and petioles of V. odorata in which callus was found throughout the leaf disk while in stem and petiole, callus was localized to the tips and terminal parts (Wijowska, 1999). Regeneration, shoot multiplication and elongation.…”
Section: Resultssupporting
confidence: 61%
“…However, the addition of auxin along with cytokinin gave positive results in petiole explant. The MS medium supplemented with 2,4-D produced a significant result using unfertilized ovules in Viola odorata [22]. Chalgeri et al [18] reported no response on callus induction of V. patrinii with higher concentrations of NAA and BAP.…”
Section: Discussionmentioning
confidence: 99%